Triazolyl Dibenzo[a, c]phenazines Stabilize Telomeric G‐quadruplex and Inhibit Telomerase. Issue 11 (12th October 2021) - Pal, Sarmistha; Fatma, Khushnood; Ravichandiran, Velayutham; Dash, Jyotirmayee
Abstract: We herein report the synthesis and biophysical evaluation of triazolyl dibenzo[ a, c ]phenazine derivatives as a novel class of G‐quadruplex ligands. The aromatic core facilitates π‐π interaction and the flexible, protonable side chains interact with the phosphate backbone of DNA via electrostatic interactions. Förster resonance energy transfer (FRET) melting assay and isothermal titration calorimetry (ITC) studies suggest that these ligands show binding preference for the hTELO G‐quadruplex over G‐quadruplexes found in the promoter region of various oncogenes and duplex DNA. The in vitro telomeric repeat amplification protocol (Q‐TRAP) assay reveals that these ligands reduce telomerase activity in cancer cells. Abstract : Bistriazolyl dibenzo[ a, c ]phenazine derivatives show high stabilization potential and exothermic binding interaction with human telomeric ( hTELO ) quadruplex over other promoter G‐quadruplexes in biophysical studies. The in vitro telomeric repeat amplification protocol (Q‐TRAP) assay reveal that they inhibit telomerase activity possibly through preferential interaction with the hTELO quadruplex.